Lessons from the development process of the Afghanistan integrated package of essential health services - Hassan Haghparast-Bidgoli; Zulfiqar A Bhutta; Karl Blanchet; Gerard Joseph Abou Jaoude; Isabelle Lange; Neha S Singh; Shafiq Mirzazada; Jolene Skordis-Worral; Teri Reynolds; Ala Alwan; Ferozuddin Feroz; Ahmad Jan Naeem; et al. (BMJ Global Health)
In 2017, in the middle of the armed conflict with the Taliban, the Ministry of Public Health decided that the Afghan health system needed a well-defined priority package of health services taking into account the increasing burden of non-communicable diseases and injuries and benefiting from the latest evidence published by DCP3. This leads to a 2-year process involving data analysis, modelling and national consultations, which produce this Integrated Package of Essential health Services (IPEHS). The IPEHS was finalised just before the takeover by the Taliban and could not be implemented. The Afghanistan experience has highlighted the need to address not only the content of a more comprehensive benefit package, but also its implementation and financing. The IPEHS could be used as a basis to help professionals and the new authorities to define their priorities.